KONSERVASI ISLAM SEBAGAI ASAS BERKARYA PRODI PENDIDIKAN SENI RUPA UNISMUH - Meisar Ashari; Andi Baetal Mukaddas (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2023)
This research aims to explain the implementation of Islamic values as educational principles in creating fine arts in the Fine Arts Education study program, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. The type of research used is qualitative-explanatory research, which provides an explanation of why the fine arts education study program uses Islamic values as an educational and teaching concept. Furthermore, the results of this research show that the only fine arts education study program within the scope of Muhammadiyah Higher Education in Indonesia is at Muhammadiyah University of Makassar. So that artistic practice in producing works of fine art is based on Islamic Kemuhammadiyahan values. The concept of application in education and teaching is demonstrated through the curriculum, art creation and study studies, research and community service as well as the achievement of graduate profiles. In the aspect of creating fine arts, the orientation of the work always uses ethics, content and context based on Islamic Muhammadiyah